2020
DOI: 10.3390/app10165413
|View full text |Cite
|
Sign up to set email alerts
|

Design of Effective Robotic Gaze-Based Social Cueing for Users in Task-Oriented Situations: How to Overcome In-Attentional Blindness?

Abstract: Robotic eye-gaze-based cueing has been studied and proved to be effective, in controlled environments, in achieving social functions as humans gaze. However, its dynamic adaptability in various real interactions has not been explored in-depth. This paper addresses a case where a simplistic robotic gaze fails to achieve effective social cueing in human–robot communication, primarily due to in-attentional blindness (IB), and presents a method that enables the robot to deliver gaze-based social signals adequately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Fukayama et al [16] measured the impressions of users interacting with a robot in different social communicating scenarios and concluded that there is a correlation between the impression and the amount of gaze, the mean duration of the gaze and the gaze points. Lee et al [17] designed a robotic gaze behavior based on social cueing for users performing quiz sessions in order to overcome inattentional blindness, with the conclusion that the robotic gaze can improve the quiz scores when participants successfully recognize the gaze-based cues performed by the robot.…”
Section: Introductionmentioning
confidence: 99%
“…Fukayama et al [16] measured the impressions of users interacting with a robot in different social communicating scenarios and concluded that there is a correlation between the impression and the amount of gaze, the mean duration of the gaze and the gaze points. Lee et al [17] designed a robotic gaze behavior based on social cueing for users performing quiz sessions in order to overcome inattentional blindness, with the conclusion that the robotic gaze can improve the quiz scores when participants successfully recognize the gaze-based cues performed by the robot.…”
Section: Introductionmentioning
confidence: 99%
“…Typical information for visualisation may include the internal status of the robot, command acknowledgement, planned trajectory, and current workspace borders. In the simplest example of such an approach, the data visualisations are displayed on 2D monitors [ 16 ] (static or hand-held tablets), which, however, require the operator to interrupt the current task and check the visualisation on display. Light projectors represent a straightforward solution for representing additional graphical clues and notifications to the operator, possibly directly in the operator’s vicinity, making it easier for the clues to be noticed [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Better user awareness can be provided by utilising notification devices (humanmachine interfaces, HMIs) that allow to understand motion plans and status of the robot. In order to convey information, these systems may utilise the primary sensory modalities of a human: vision (monitors [6], light projectors [7,8], mixed reality devices [9][10][11]), hearing (sound alerts and speech notifications [2,12]), touch (tactile feedback devices [4,[13][14][15]). Touch modality represents a robust and direct way of transferring information to the user, making it suitable to convey information to workers in industrial environments, where visual and auditory modalities might be busy or blocked.…”
Section: Introductionmentioning
confidence: 99%